Influence of new dental elixir on rats periodontal tissues with modeling of metabolic syndrome - Kravchenko, L. S.; Koval, S. N.; Plotnikova, V. G.; Bila, N. F.; Zherebko, A. N.; Ivanova, Ya. I. (Journal of Education, Health and Sport, 2021)
Aim: to study the changes in the periodontal tissues of rats with simulation of metabolic syndrome of alimentary genesis and to determine a possibility of their correction with the new dental elixir. Materials and methods: Biochemical changes in the blood serum, liver and gingival tissue were examined during simulation of the metabolic syndrome of alimentary genesis in experiment on 28 white male rats of reproductive age with an average body weight (280±14)g. Results. It was found that keeping animals for ten weeks on a diet high in saturated fats and carbohydrates led to increase in body weight and in level of biochemical markers: insulin resistance, hyperglycemia, inflammation, both at the level of the body and locally in the periodontal tissues. Local application of the new dental elixir in the form of applications to rats gums against the background of metabolic syndrome reduced the level of triglycerides, had an anti-inflammatory and antioxidant effect, reducing contamination by pathogenic microflora (urease activity), lipid peroxidation activity (malonic dialdehyde content), activating locally in the periodontal tissues the antioxidant defense enzyme and nonspecific immunity — lysozyme. Conclusions. The use of the new oral hygiene product in experimental metabolic syndrome improved metabolism, reduced inflammation, presenting periodontal protective properties, which allows to offer it for clinical testing in patients with periodontitis against a background of metabolic syndrome.